Massive Penetrating Craniofacial Trauma due to Polyvinyl Chloride Pipe - Somashekhar Srinivas; Amit Agrawal; Yashawant Sandeep; Ninad Nareschandra Shrikhande (Indian Journal of Neurosurgery)
Penetrating craniofacial trauma can lead to massive injury to the facial tissue and craniofacial skeleton with retained bone as well as foreign body. We present a case of 45-year-old man who sustained massive penetrating craniofacial injuries due to polyvinyl chloride (PVC) pipe. CT scan with bone window of the brain and craniofacial region showed in driven fragment of PVC pipe into the nasal cavity with multiple fractures and soft tissue swelling. CT brain showed compound and comminuted depressed fracture of the right frontal bone with underlying contusion of the brain and specks of pneumocephalus. However, detailed examination of the CT scan showed that there was no breach in the anterior cranial fossa and that both the injuries were caused by separate pipe fragments. The wound was debrided; all loose bone fragments, necrotic brain matter, and broken pipe fragments were removed. The patient recovered well after surgical procedure. The approach is aimed to protect the airway, maintain vital parameters followed by remove all the foreign body and necrotic tissue, and restore the functioning and aesthetics. A careful evaluation of the CT scan is mandatory to rule out breach in the skull base, and if the skull base is intact, a limited craniotomy will save the time and associated morbidity.